2015
DOI: 10.1021/es506214c
|View full text |Cite
|
Sign up to set email alerts
|

Computational Design of Biomimetic Phosphate Scavengers

Abstract: 21Phosphorous has long been the target of much research, but in recent years the focus has 22shifted from being limited only to reducing its detrimental environmental impact, to also looking 23 at how it is linked to the global food security. Therefore, the interest in finding novel techniques 24 for phosphorous recovery, as well as improving existing techniques, has increased. In this study 25we apply a hybrid simulation approach of molecular dynamics and quantum mechanics to 26 investigate the binding modes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 65 publications
2
19
1
Order By: Relevance
“…This is in accordance with a previous study where similar constructs (SGA GKT) of the peptides were investigated by MD [35]. Here the peptide of inspiration (SGA GKT) was studied as peptide-only and peptide-phosphate systems.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…This is in accordance with a previous study where similar constructs (SGA GKT) of the peptides were investigated by MD [35]. Here the peptide of inspiration (SGA GKT) was studied as peptide-only and peptide-phosphate systems.…”
Section: Resultssupporting
confidence: 87%
“…Here the peptide of inspiration (SGA GKT) was studied as peptide-only and peptide-phosphate systems. The peptide conformational ensemble was stabilized by the presence of a phosphate anion, however the isolated peptide was likely to spend most of the time in a disordered state [35]. Thus, it is expected that the peptide will exhibit a flexible structure when in contact with the membrane matrix.…”
Section: Resultsmentioning
confidence: 99%
“…The link between global food security and biomimetic research is grounded on the progress made using biomimetic approaches to address water scarcity, using inexpensive and scalable Warka and water cone water from the atmosphere [ 28 ]. Additionally, biomimetic approaches have led to the development of biomimetic phosphate scavengers via quantum chemical studies of phosphate anions on small, intrinsically disordered peptides [ 29 ]. The latter study demonstrated that it was possible to improve global food security using phosphate scavengers while minimizing the negative effect of phosphate compounds on the environment.…”
Section: Introductionmentioning
confidence: 99%
“…14,[23][24][25] However, for highly charged species like phosphates-containing ligands, the actual charge distributions of atoms and their changes in response to the environment's electric field is complicated and challenging to model and simulate. [26][27][28][29][30][31][32] Recently, polarizable force fields have shown encouraging results for depicting these complicated interactions. [33][34] As a physics-grounded force field, AMOEBA depicts molecular polarizability and electrostatic potential terms by using mutual atomic dipole-dipole induction along with permanent atomic point multipoles up to quadrupole.…”
Section: Introductionmentioning
confidence: 99%